Genetic Regulation of Development in Sorghum bicolor (X. Greatly Attenuated Photoperiod Sensitivity in a Phytochrome-Deficient Sorghum Possessing a Biological Clock but Lacking a Red Light-High Irradiance Response). - Childs, K. L. (1995)
The role of a light-stable, 123-kD phytochrome in the biological clock, in photoperiodic flowering and shoot growth in extended photoperiods, and in the red light-high irradiance response was studied in Sorghum bicolor using a phytochrome-deficient mutant, 58M (ma3R ma3R), and a near-isogenic wild-type cultivar, 100M (Ma3 Ma3). Since chlorophyll a/b-binding protein mRNA and ribulose bisphosphate carboxylase small subunit mRNA cycled in a circadian fashion in both 58M and 100M grown in constant light, the 123-kD phytochrome absent from 58M does not appear necessary for expression or entrainment of a functional biological clock. Although 58M previously appeared photoperiod insensitive in 12-h photoperiods, extending the photoperiod up to 24 h delayed floral initiation for up to 2 weeks but did not much affect shoot elongation. Thus, although 58M flowers early in intermediate photoperiods, a residual photoperiod sensitivity remains that presumably is not due to the missing 123-kD phytochrome. Since rapid shoot elongation persists in 58M under extended photoperiods despite delayed floral initiation, long photoperiods uncouple those processes. The observed absence of a red light-high irradiance response in 58M, in contrast to the presence of the response in 100M, strengthens the suggestion that the 123-kD phytochrome missing from 58M is a phyB.